Analysis of Adolescent Intention Factors in Drug Abuse Prevention in Tuban District - Roudlotul Jannah; Wahyuningsih Triana Nugraheni; Wahyu Tri Ningsih; Ellen Rygh; Yasmin Asih Scheiber (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Drug abuse among adolescents was currently increased, it’s important to prevention. Tuban district in 2018 trend of drug cases a significant increased. Data from the Tuban Police, there was an increased in cases up to 173.68 percent when compared to similar cases in 2017. The purpose of this study was to determine the determinant factors that influence adolescents' intentions to prevent drug abuse, which will contribute to policy making related to drug prevention among adolescents. Methods: Design of this study used descriptive correlation with a cross-sectional approach. The population were all students in junior high schools in Tuban, an affordable target population of 1880 students. Sample were 200 students, taken by quota sampling according inclusion and exclusion criteria. Data collected by questionnaire. Data collected was tabulated, analyzed using frequency and percentage distributions and presented in distribution table. Bivariate and multivariate analysis used logistic regression test to analyzed the determinants factors. Results of this study show that attitudes and gender were factors that influenced adolescents’ intention to prevent drug abuse, attitude (p value=0.001) and gender (p value=0.034). Conclusion: From this study, we can be concluded that the attitude and gender were factors that influence adolescents’ intention to prevent drug abuse. Implication: Increased intention to prevent drug abuse requires efforts to lead to a more positive attitude of youth by providing training; health education, the formation of anti-drug ambassadors among young men and women an early age in a planned and periodic manner with the relevant agencies.